Cancer prevention awareness among young adult Polish females on the basis of the assessment of knowledge and health behaviours - Wiraszka, Grażyna R.; Góral, Katarzyna; Stępień, Renata B.; Kielar, Maciej (Medical Studies/Studia Medyczne, 2016)
Introduction: The accelerating rate of incidence of malignant cancers in Polish women as compared to men and the higher mortality due to these diseases as compared to other regions in Europe is an important medical and social problem. Aim of the research : To attempt an assessment of cancer prevention awareness among young adult Polish females on the basis of the analysis of their knowledge as well as of the prevalence of negative health behaviours. Material and methods : The study was conducted in 270 young Polish females: students of nursing and pedagogy. The study was conducted using a proprietary questionnaire, the Inventory of Health Behaviour, the Fagerström Test for Nicotine Dependence, and Nina Schenider’s Motivation for Quitting Smoking Test. Results : The highest percentages of negative behaviours included low intake of fruit and vegetables (76.3%), whole-grain products (78.9%), and fish (93.3%), as well as tanning (56.7%) and smoking (37%) and health check behaviours (breast self-exams 60.7%, cervical cytological screening 36%). Conclusions: Despite the relatively high level of knowledge, cancer risk-related lifestyles and behaviours unfavourable for the possibility of early diagnosis were observed among the subjects. The less favourable model of cognitive and behavioural competence in health and cancer prevention was observed at bachelor-level students of pedagogy at the ages below 24 years. Development of skills and motivation for pro-health behaviours and the awareness of behaviour models presented by educators are, along with appropriate knowledge, the most desirable strategies for the success of health education in the area of cancer prevention.